Weibo Attention and Stock Market Performance: Some Empirical Evidence. (3rd September 2018) - Dong, Minghua; Xiong, Xiong; Li, Xiao; Shen, Dehua
Abstract : In this paper, we employ Weibo Index as the proxy for investor attention and analyze the relationships between investor attention and stock market performance, i.e., trading volume, return, and volatility. The empirical results firstly show that Weibo attention is positively related to trading volume, intraday volatility, and return. Secondly, there exist bidirectional causal relationships between Weibo attention and stock market performance. Thirdly, we generally find that higher Weibo attention indicates higher correlation coefficients with the quantile regression analysis.